Interactive directory using augmented reality in shopping mall - Chan, Jia Ee (Universiti Malaysia Sarawak, (UNIMAS), 2015)
In a shopping mall, directory plays an important role in guiding people to their destination and provides related details about the location of destination in the shopping mall. In this research, Augmented Reality (AR) technology is applied in the directory of shopping mall in order to provide the users a more interesting and remarkable experience when they are using the directory in the shopping mall. Besides, the virtual 3D models or objects that appear on the AR directory give a more entertaining experience to the users compared to the conventional directory in shopping mall. Therefore, the interactive AR directory that combined virtual objects with real world environment enables users to memorise the location and related details of their destination better through the interactivity experience with the interactive AR directory. In the system of interactive AR directory, the shops’ logo is used as the image target and the virtual objects that involved are the related 3D models and information of the shop. On the other hand, in this research, Rapid Application Development (RAD) model is used to develop the system and technical evaluation is conducted in order to test the system’s usability and understand how several issues such as the markers’ orientation, lighting conditions, phone camera’s resolution, and so on can affect the efficiency of the interactive AR directory.